Capitalizing on the Most Important Part of a Learning Session: The Experience. (February 2018) - Clapper, Timothy C.
The experience is the most important part of the learning process. For learning to occur, the learner must do something with the information and reflect on the content throughout the process. To maximize the learning experience, we need to provide opportunities for reflection, both in-action, and on-action. As Montessori showed us long ago, the resources and experiences provided in the safe, properly prepared learning environment can create multiple opportunities for growth.